2010
DOI: 10.1016/j.ejso.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective longitudinal study of quality of life following cytoreductive surgery and intraperitoneal chemotherapy for pseudomyxoma peritonei

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…alves et al 20 published results of a prospective longitudinal study from this tertiary center looking at Qol, before and at intervals up to a year following surgery, and hiPeC in patients with PmP. univariate and multivariate analysis in this group showed that there are subgroups who derive maximum benefit, and, as outlined, patients with high-grade tumors have the worst outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…alves et al 20 published results of a prospective longitudinal study from this tertiary center looking at Qol, before and at intervals up to a year following surgery, and hiPeC in patients with PmP. univariate and multivariate analysis in this group showed that there are subgroups who derive maximum benefit, and, as outlined, patients with high-grade tumors have the worst outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in complete CRS rates has been a culmination of technical experience and personal observation on the benefits of complete CRS in quality and quantity of life. Where extensive small bowel involvement precludes complete CRS the benefit of MTD, particularly in patients with PMP, has yielded good quality of life and long‐term survival in many patients .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment related postoperative grade [3][4][5] complications mainly surgery related developed in 4 patients (17.3%) that consisted of leakage in 2 patients, pulmonary embolism, and reactionary hemorrhage. Operative mortality was 22.2% (n=6).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…This is combined with IPEC that targets the microscopic residual disease and free neoplastic cells in the peritoneal cavity. This chemotherapy may be heated (hyperthermic) (HIPEC), which is used intraoperatively; or this can be used either preoperatively or early postoperative [3]. Retrospective studies have shown that debulking procedures alone can provide 5-year survival rates of 55% -75%, however, around 90% of patients have disease recurrence within 2 years and will often require multiple debulking procedures [4].…”
Section: Introductionmentioning
confidence: 99%